High-smoothness collision-resistant polyester shrink film as well as preparation method and application thereof

Through one -step method, water thermal law preparation metal phase dispermine@graphene ellipsoid hybrid composite material and introduce polyester substrates to solve the problem of polyester materials on the friction surface and easily wear, realize the significant significant high, smooth and bump performance, Improving and the maintenance of optical properties, and has the characteristics of low cost and suitable for industrial production.

CN119331395AActive Publication Date: 2025-01-21HENAN YINJINDA NEW MATERIALS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411450635.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-21
Estimated Expiration
2044-10-17

AI Technical Summary

Technical Problem

The existing polyester materials are prone to wear on the friction surface, reduce transparency, and are difficult to take into account both the production cost and the mechanical, friction and optical properties.

Method used

A one-step hydrothermal method was used to prepare the metallic phase molybdenum disulfide@graphene ellipsoid hybrid composite material, and introduced it into the polyester matrix to enhance the high smoothness and anti-collision properties of the polyester material through the synergistic effect of nanoparticles.

Benefits of technology

It significantly reduces the friction coefficient and wear rate of polyester materials, improves wear resistance and optics, and has a simple preparation process, low cost, and suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119331395A_ABST
    Figure CN119331395A_ABST
Patent Text Reader

Abstract

The invention relates to a high-smoothness collision-resistant polyester shrink film as well as a preparation method and application thereof, a method for preparing a metal phase molybdenum disulfide and graphene ellipsoid hybrid composite material in situ in one step is adopted, and the composite material is introduced into a polyester shrink film matrix; the high-smoothness collision-resistant polyester shrink film composite material with excellent performance is obtained. By means of the excellent performance of the metal phase molybdenum disulfide and the graphene sheet layer, preparation of the high-smoothness collision-resistant polyester shrink film composite material is achieved; the friction coefficient of the prepared high-smoothness collision-resistant polyester shrink film can be reduced to 0.0952, the wear rate can be reduced to 0.229 * 10 <-5 > mm < 3 > / Nm, the light transmittance has no significant change after 100 times of impact tests, and the high-smoothness collision-resistant polyester shrink film can be widely applied to wear-resistant and friction-resistant polyester shrink film composite materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polyester shrinkage films, in particular to a highly smooth and bump-resistant polyester shrinkage film with synergistic effect of nanoparticles and a preparation method and application thereof. Background Art

[0002] Polyester materials have excellent creep resistance, heat resistance, fatigue resistance, impact resistance and transparency, and are widely used in shrink film materials, bottle sheets, fibers, engineering plastics and other fields. In addition, polyester is also widely used in kitchen appliances, food packaging, and automobile manufacturing. It is a basic material that meets the needs of the national economy. However, the wear rate of polyester materials is high, and its transparency is heavily dependent on surface protection. Its outer surface is very easy to be worn, causing a serious reduction in transmittance. Therefore, various fillers such as nanoparticles, fibers, solid lubricants, etc. are usually added to polyester materials to obtain composite materials with better mechanical properties, tribological properties and optical properties.

[0003] There are already literature reports on the use of different fillers to improve the friction properties of polyester materials. For example, Wang Haosheng et al. studied the effects of alumina morphology and particle size on the performance of epoxy-polyester nanocomposite wear-resistant coatings and found that alumina particles of different particle sizes can improve the wear resistance of the coating. Under the same filling amount, the specific wear rate of the small-particle composite coating is higher than that of the large-particle alumina coating (New Chemical Materials, 2019, 10: 101-104). Mou Qiuhong et al. studied the preparation and wear resistance of unsaturated polyester / sisal fiber composites and found that the wear resistance of the composite material was 68% higher than that of the untreated system; the wear resistance of the composite material improved with the increase of sisal fiber content (Journal of Guilin Institute of Technology, 2005, 25: 198-201). Although there are literature reports on the wear resistance of nanoparticles or fiber-reinforced polyester, there are few reports on the use of double nanoparticles to synergistically enhance the wear resistance and bump resistance of polyester. Molybdenum disulfide is widely used in friction materials. The weak interaction between the layers of molybdenum disulfide with a lamellar structure makes it easy for interlayer slip to occur, so it has good lubrication properties. Molybdenum disulfide has multiple phases, including 1T, 2H and 3R. Among them, 1T molybdenum disulfide is also called metallic phase molybdenum disulfide. Compared with the other two types of molybdenum disulfide, it has a larger interlayer spacing and is expected to have better lubrication properties. The existing technology is usually 2H phase molybdenum disulfide, and there is no report on the use of metallic phase molybdenum disulfide and graphene composites as high-slip and bump-resistant polyester shrink film materials. Summary of the invention

[0004] In order to solve the above problems, the purpose of the present invention is to provide a highly smooth and bump-resistant polyester shrink film and a preparation method and application thereof. A variety of nanoparticles often have a synergistic effect, and exert a practical effect of 1+1 greater than 2. Therefore, the present invention adopts a one-step method for the first time to prepare a metal phase molybdenum disulfide and graphene composite material, and utilizes the synergistic effect between nanoparticles to enhance the high smoothness and bump resistance of the polyester material, thereby preparing a polyester composite material with low cost, simple synthesis route and excellent friction performance, thereby solving the problem that the existing polyester composite material cannot take into account both the preparation cost and the mechanical, friction and optical properties.

[0005] A method for preparing a highly smooth and bump-resistant polyester shrink film according to the present invention specifically comprises the following steps:

[0006] (1) Preparing a metal phase molybdenum disulfide @ graphene ellipsoid hybrid composite material: 35-40 ml of distilled water and 5-10 ml of ethanol are uniformly mixed to obtain an ethanol solution, graphene oxide, ammonium molybdate and thiourea are dispersed in the ethanol solution to obtain a solution A, the solution A is transferred to a hydrothermal autoclave, reacted at a temperature of 180-200° C. for 16-24 hours, cooled to room temperature after the reaction is completed, the reacted solution is filtered through a cellulose filter membrane, and the solid obtained by filtration is dried to obtain a metal phase molybdenum disulfide @ graphene ellipsoid hybrid composite material;

[0007] (2) The metal phase molybdenum disulfide@graphene ellipsoid hybrid composite material and the polyester matrix obtained in step (1) are taken as raw materials, added into a high-speed mixer for mixing, and then transferred into a twin-screw extruder for melt blending, extrusion granulation, and injection molding to obtain a highly smooth and bump-resistant polyester shrink film composite material.

[0008] Furthermore, in step (1), the mass of graphene oxide is 0.10 g, the mass of ammonium molybdate is 1.25 g, and the mass of thiourea is 1.00 g.

[0009] Furthermore, the polyester matrix in step (2) is one or more of polybutylene terephthalate, polyethylene terephthalate, polypropylene terephthalate, polybutylene succinate adipate, and polybutylene succinate. The metal phase molybdenum disulfide@graphene ellipsoid hybrid composite material can be widely used in other polyester materials.

[0010] Furthermore, in step (2), the mass of the metal phase molybdenum disulfide@graphene ellipsoid hybrid composite material accounts for 1-5% of the total mass of the raw materials.

[0011] Furthermore, in step (2), the mixing time of the raw materials in the high-speed mixer is 10 minutes.

[0012] Furthermore, in step (2), the time for melt blending is 2-8 minutes, and the temperature for extrusion granulation is 200-240°C.

[0013] Furthermore, in step (2), the injection molding pressure is 80 MPa, and the injection molding temperature is 240°C.

[0014] Furthermore, the metal phase molybdenum disulfide@graphene ellipsoid hybrid composite material obtained in step (1) has an ellipsoidal morphology. By changing the reaction conditions, nanomaterials with other morphologies and structures can be obtained, such as the technology mentioned in the background technology.

[0015] In step (1), a distilled water-ethanol mixed solvent is used as a reaction solvent, thiourea is used as a reducing agent, and the introduction of ethanol has a decisive effect on the morphology of the product; using other solvents and reducing agents will obtain nanomaterials with different structures and morphologies. For example, the widely reported molybdenum disulfide usually uses thioacetamide as a reducing agent and distilled water as a solvent, and usually obtains 2H phase molybdenum disulfide.

[0016] The present invention also provides a highly smooth and bump-resistant polyester shrink film composite material obtained according to the preparation method and application of the highly smooth and bump-resistant polyester shrink film composite material in the field of shrink film materials.

[0017] The high slip and bump resistance of the composite material is achieved by the synergistic effect of nanoparticles.

[0018] In the present invention, the lamellar flexible graphene sheets and the rigid molybdenum disulfide sheets are adsorbed to each other to form an ellipsoidal composite material. The use of ethanol solvent has a significant effect on the morphology of the molybdenum disulfide@graphene composite material; the key to the formation of metal phase molybdenum disulfide is the hydrothermal temperature and time. The metal phase molybdenum disulfide@graphene obtained in the present application has an ellipsoidal morphology, such as Figure 1 As shown, the graphene sheets and the metal phase MoS2 adsorb each other, and the overlapping graphene and MoS2 sheets are peeled off under the shearing action of the friction surface, and then adsorbed to the surface of the friction pair to form a protective film.

[0019] The present invention discloses a method for preparing a highly smooth and bump-resistant polyester shrink film composite material. First, a metal phase molybdenum disulfide @ graphene ellipsoid hybrid composite material is prepared by a one-step hydrothermal method, and then the metal phase molybdenum disulfide @ graphene ellipsoid hybrid composite material is introduced into a polyester matrix, so that a "micro bearing" can be obtained on the friction surface, and a polyester composite material with excellent friction performance can be obtained. Under the huge shear force of the friction surface, the metal phase molybdenum disulfide @ graphene ellipsoid hybrid composite material is peeled off, and while the load is effectively dispersed, a single layer of metal phase molybdenum disulfide and graphene sheet is obtained, and the above-mentioned single layer material will be adsorbed to the friction surface to form a protective film. The above-mentioned high smoothness is reflected in the low friction coefficient of the polyester composite material, and the composite material has a low friction coefficient; the bump-resistant performance is reflected in the good wear resistance of the composite material. With the improvement of the wear resistance, the polyester shrink film is not easy to be scratched on the surface, thereby improving the optical performance of the composite material under different service conditions.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] (1) The present invention discloses a highly smooth and bump-resistant polyester shrink film composite material with synergistic nanoparticles and a preparation method thereof. The metal phase molybdenum disulfide@graphene ellipsoid hybrid composite material with synergistic wear-resistant effect is in-situ compounded by a one-step hydrothermal method, and the preparation process is simple. The composite material is introduced into a polyester matrix to obtain a wear-resistant composite material. Graphene sheets are easy to form a physical protective film and molybdenum disulfide sheets are easy to form a chemical protective film. Under the synergistic effect of the double protective films, the friction performance of the friction pair is greatly improved; under the huge shearing effect of the friction surface, the metal phase molybdenum disulfide and graphene slip relatively, and the exfoliated molybdenum disulfide and graphene sheets will be adsorbed to the friction surface to form a chemical friction film, which can greatly reduce the wear of the polyester; at the same time, the ellipsoidal composite material can form a "micro bearing" on the friction surface to carry the load and improve the tribological performance. Finally, the added nanoparticles can reduce the surface energy of the material, reduce the interfacial interaction force, and improve the optical properties of the material after multiple collisions. The friction coefficient of the polyester composite material prepared by the present invention can be reduced from 0.258 of pure polyester to 0.0952, and the wear rate can be reduced from 0.350×10 -5 mm 3 / N m can be reduced to 0.229×10 -5 mm 3 / Nm, after the impact test of the polyester shrink film material, its optical transmittance remained above 98%, and there was no significant change in the transmittance after 100 impact tests.

[0022] (2) The present invention prepares metallic phase molybdenum disulfide@graphene by a one-step method, which has a simple route, a large specific surface area of ​​the sheet, and is easy to adsorb on the friction surface. It can greatly increase the friction performance of polyester and also has significant economic benefits. The method of the present invention is simple, low-cost, and easy to realize large-scale industrial production. It has significant economic benefits and can be widely used in the field of high-slip and bump-resistant polyester shrink film composite materials, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 is a morphology image of the ellipsoidal metal phase molybdenum disulfide@graphene prepared in Example 1 of the present invention;

[0024] Figure 2 This is a wear surface morphology image of the highly smooth and bump-resistant polyester shrink film prepared in Example 1 of the present invention;

[0025] Figure 3 This is a wear surface morphology of the highly smooth and impact-resistant polyester shrink film prepared in Comparative Example 2. DETAILED DESCRIPTION

[0026] In order to better understand the content of the present invention, the present invention will be further described below in conjunction with specific embodiments and drawings. The following embodiments are implemented based on the technology of the present invention, and detailed implementation methods and operating steps are given, but the protection scope of the present invention is not limited to the following embodiments.

[0027] The ethanol used in the examples and comparative examples was analytical grade ethanol.

[0028] Embodiment 1:

[0029] (1) 40 ml of distilled water and 5 ml of ethanol were uniformly mixed to obtain an ethanol solution, 0.10 g of graphene oxide, 1.25 g of ammonium molybdate and 1.00 g of thiourea were dispersed in the ethanol solution to obtain a solution A, the solution A was transferred to a hydrothermal reactor, reacted at 200° C. for 20 hours, cooled to room temperature after the reaction, filtered through a cellulose filter membrane, and dried the solid obtained by filtration to obtain a metal phase molybdenum disulfide@graphene ellipsoid hybrid composite material;

[0030] (2) Taking 5 parts of the metal phase molybdenum disulfide@graphene ellipsoid hybrid composite material obtained in step (1) and 95 parts of polyester particles by weight, adding them to a high-speed mixer and mixing for 10 minutes, then transferring them to a twin-screw extruder for melt blending, extrusion granulation, and injection molding to obtain a highly smooth and bump-resistant polyester shrink film, wherein the twin-screw extruder melt blending time is 6 minutes, the extrusion granulation temperature is 220°C, the injection molding pressure is 80 MPa, the injection molding temperature is 240°C, and the polyester particles are polyethylene terephthalate particles.

[0031] Embodiment 2:

[0032] (1) This step is the same as step (1) of Example 1;

[0033] (2) Taking 4 parts of the metal phase molybdenum disulfide@graphene ellipsoid hybrid composite material obtained in step (1) and 96 parts of polyester particles by weight, adding them to a high-speed mixer and mixing for 10 minutes, then transferring them to a twin-screw extruder for melt blending, extrusion granulation, and injection molding to obtain a highly smooth and bump-resistant polyester shrink film, wherein the twin-screw extruder melt blending time is 6 minutes, the extrusion granulation temperature is 220°C, the injection molding pressure is 80MPa, the injection molding temperature is 240°C, and the polyester particles are polybutylene terephthalate particles.

[0034] Embodiment 3:

[0035] (1) This step is the same as step (1) of Example 1;

[0036] (2) Taking 3 parts of the metal phase molybdenum disulfide@graphene ellipsoid hybrid composite material obtained in step (1) and 97 parts of polyester particles by weight, adding them to a high-speed mixer and mixing for 10 minutes, then transferring them to a twin-screw extruder for melt blending, extrusion granulation, and injection molding to obtain a highly smooth and bump-resistant polyester shrink film, wherein the twin-screw extruder melt blending time is 6 minutes, the extrusion granulation temperature is 220°C, the injection molding pressure is 80 MPa, the injection molding temperature is 240°C, and the polyester particles are polytrimethylene terephthalate particles.

[0037] Embodiment 4:

[0038] (1) This step is the same as step (1) of Example 1;

[0039] (2) Taking 1 part of the metal phase molybdenum disulfide@graphene ellipsoid hybrid composite material obtained in step (1) and 99 parts of polyester particles by weight, adding them to a high-speed mixer and mixing for 10 minutes, then transferring them to a twin-screw extruder for melt blending, extrusion granulation, and injection molding to obtain a highly smooth and bump-resistant polyester shrink film, wherein the twin-screw extruder melt blending time is 2 minutes, the extrusion granulation temperature is 220°C, the injection molding pressure is 80 MPa, the injection molding temperature is 240°C, and the polyester particles are polybutylene terephthalate particles.

[0040] Comparative Example 1:

[0041] 100 parts of polyester granules were taken by weight, added to a high-speed mixer and mixed for 10 minutes, and then transferred to a twin-screw extruder for melt blending, extrusion granulation, and injection molding to obtain a highly smooth and bump-resistant polyester shrink film composite material, wherein the twin-screw extruder melt blending time was 6 minutes, the extrusion granulation temperature was 220°C, the injection molding pressure was 80MPa, and the injection molding temperature was 240°C.

[0042] Comparative Example 2:

[0043] (1) 0.10 g of graphene oxide, 1.25 g of ammonium molybdate and 1.00 g of thiourea were dispersed in 50 ml of distilled water to obtain solution B, solution B was transferred to a hydrothermal autoclave, reacted at 200° C. for 20 hours, cooled to room temperature after the reaction, filtered through a cellulose filter membrane, and the solid obtained by filtration was dried to obtain a conventional 2H molybdenum disulfide@graphene hybrid composite material.

[0044] (2) Taking 5 parts of the 2H molybdenum disulfide@graphene hybrid composite material obtained in step (1) and 95 parts of polyester particles by weight, adding them to a high-speed mixer and mixing for 10 minutes, then transferring them to a twin-screw extruder for melt blending, extrusion granulation, and injection molding to obtain a highly smooth and bump-resistant polyester shrink film composite material, wherein the twin-screw extruder melt blending time is 6 minutes, the extrusion granulation temperature is 220°C, the injection molding pressure is 80MPa, and the injection molding temperature is 240°C.

[0045] The tribological properties of the high-smooth and anti-collision polyester shrink film were tested using an MM-W1 four-ball friction tester. The friction and wear test conditions were 1.648GPa and 1000rpm, and the test time was 30 minutes. The steel ball was GCr15 bearing steel (diameter: 12.7mm). Three repeated friction and wear tests were carried out under the experimental conditions, and the performance data obtained from the three repeated tests were averaged.

[0046] Table 1 Performance of high-smooth and anti-collision polyester shrink films prepared in Examples 1-4 and Comparative Examples 1-2

[0047]

[0048] It can be seen from Table 1 that adding metal phase molybdenum disulfide @ graphene ellipsoid hybrid composite material to polyester matrix can significantly improve the friction performance of polyester. In Example 1, the addition ratio of metal phase molybdenum disulfide @ graphene ellipsoid hybrid composite material is 5% of polyester. In Examples 1-4, as the addition amount of metal phase molybdenum disulfide @ graphene ellipsoid hybrid composite material increases, the friction coefficient of the polyester composite material gradually decreases, and the wear rate also shows a decreasing trend, that is, the friction resistance gradually improves; at the same time, it can also be found that as the content of metal phase molybdenum disulfide @ graphene ellipsoid hybrid composite material continues to increase, the wear resistance of the polyester composite material improves at a slower rate; this may be because when the concentration of metal phase molybdenum disulfide @ graphene ellipsoid hybrid composite material increases, a small amount of exfoliated molybdenum disulfide and graphene sheets agglomerate, resulting in a slowdown in the wear resistance improvement rate.

[0049] When the weight of the metal phase molybdenum disulfide @ graphene ellipsoid hybrid composite material in the polyester composite material is 5%, the metal phase molybdenum disulfide @ graphene ellipsoid hybrid composite material is peeled off under the shearing action of the friction surface to generate free molybdenum disulfide flakes and graphene flakes. Due to the large specific surface area of ​​the above flakes, they are easily adsorbed on the friction surface of the friction pair to form a physical and chemical protective film, thereby reducing the friction coefficient and wear rate, and showing the best wear resistance; continuing to increase the content of the metal phase molybdenum disulfide @ graphene ellipsoid hybrid composite material, the peeled molybdenum disulfide and graphene flakes are easy to agglomerate, so as the content of the metal phase molybdenum disulfide @ graphene ellipsoid hybrid composite material increases, the increase rate of wear resistance slows down; from the above data, it can be seen that the prepared metal phase molybdenum disulfide @ graphene ellipsoid hybrid composite material has good lubrication properties, and adding a small amount (about 2%) can significantly improve the friction performance of the polyester composite material. Therefore, the prepared metal phase molybdenum disulfide @ graphene ellipsoid hybrid composite material is a good solid lubricant additive and can be used as a wear-resistant additive for polyester materials. Comparative Example 2 shows that compared with 2H phase molybdenum disulfide nanomaterials, metal phase molybdenum disulfide nanocomposites have more excellent tribological properties. The prepared polyester film material is horizontally fixed on the mold, and a steel ball (6.35mm) is freely dropped at a height of 1 meter from it. The transmittance of the polyester shrink film is tested after the ball hits 100 times to characterize its anti-collision performance. It can be seen from Table 1 that, unlike the comparative example, the embodiment material has a significantly improved light transmittance of the shrink film material after the ball hits the polyester shrink film with the decrease of the friction coefficient and the improvement of the wear resistance, indicating that the shrink film prepared by the present application has good anti-collision performance.

[0050] Figure 1 is a morphology diagram of the ellipsoidal metal phase molybdenum disulfide@graphene obtained in Example 1 of the present invention; Figure 1 It can be seen that the soft graphene sheets are compounded with the rigid metal phase MoS2, and the two form a unique ellipsoidal morphology.

[0051] Figure 2 This is a wear surface morphology of the highly smooth and bump-resistant polyester shrink film composite material prepared in Example 1 of the present invention. Figure 2 It can be seen that the metal phase MoS2@graphene ellipsoid hybrid composite material is uniformly dispersed in the matrix, thereby providing good anti-wear and friction-reducing properties on the friction surface.

[0052] Figure 3 This is a wear surface morphology of the highly smooth and bump-resistant polyester shrink film composite material prepared in Comparative Example 2. Figure 3 It can be seen that the composite material has obvious tearing behavior, which indirectly reflects the excellent friction properties of the high-slip and anti-collision polyester shrink film composite material prepared by the metal phase molybdenum disulfide@graphene hybrid composite material.

[0053] The above is only an embodiment of the present invention, and does not limit the present invention in any form. The present invention can also have other forms of embodiments according to the above structures and functions, which are not listed one by one. Therefore, any simple modification, equivalent change and modification made by any technician familiar with the profession to the above embodiment according to the technical essence of the present invention without departing from the scope of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A highly smooth and bump-resistant polyester shrink film and a preparation method thereof, characterized in that: The specific steps include: (1) Preparing a metal phase molybdenum disulfide @ graphene ellipsoid hybrid composite material: 35-40 ml of distilled water and 5-10 ml of ethanol are uniformly mixed to obtain an ethanol solution, graphene oxide, ammonium molybdate and thiourea are dispersed in the ethanol solution to obtain a solution A, the solution A is transferred to a hydrothermal autoclave, reacted at a temperature of 180-200° C. for 16-24 hours, cooled to room temperature after the reaction is completed, the reacted solution is filtered through a cellulose filter membrane, and the solid obtained by filtration is dried to obtain a metal phase molybdenum disulfide @ graphene ellipsoid hybrid composite material; (2) The metal phase molybdenum disulfide@graphene ellipsoid hybrid composite material and the polyester matrix obtained in step (1) are taken as raw materials, added into a high-speed mixer for mixing, and then transferred into a twin-screw extruder for melt blending, extrusion granulation, and injection molding to obtain a highly smooth and bump-resistant polyester shrink film.

2. The method for preparing a highly smooth and bump-resistant polyester shrink film according to claim 1, characterized in that: In step (1), the mass of graphene oxide is 0.10 g, the mass of ammonium molybdate is 1.25 g, and the mass of thiourea is 1.00 g.

3. The method for preparing a highly smooth and bump-resistant polyester shrink film according to claim 1, characterized in that: The polyester matrix in step (2) is one or more of polybutylene terephthalate, polyethylene terephthalate, polypropylene terephthalate, polybutylene succinate adipate, and polybutylene succinate.

4. The method for preparing a highly smooth and bump-resistant polyester shrink film according to claim 1, characterized in that: In step (2), the mass of the metal phase molybdenum disulfide@graphene ellipsoid hybrid composite material accounts for 1-5% of the total mass of the raw materials.

5. The method for preparing a highly smooth and bump-resistant polyester shrink film according to claim 1, characterized in that: The mixing time of the raw materials in the high-speed mixer in step (2) is 10 minutes.

6. The method for preparing a highly smooth and bump-resistant polyester shrink film according to claim 1, characterized in that: The time of melt blending in step (2) is 2-8 minutes, and the temperature of extrusion granulation is 200-240°C.

7. The method for preparing a highly smooth and bump-resistant polyester shrink film according to claim 1, characterized in that: The injection molding pressure in step (2) is 80 MPa, and the injection molding temperature is 240°C.

8. The method for preparing a highly smooth and bump-resistant polyester shrink film according to claim 1, characterized in that: The metal phase molybdenum disulfide@graphene ellipsoidal hybrid composite material obtained in the step (1) has an ellipsoidal morphology.

9. A highly smooth and bump-resistant polyester shrink film prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the highly smooth and bump-resistant polyester shrink film according to claim 9 in the field of shrink film materials.

Citation Information

Patent Citations

  • Method for 1T-phase molybdenum disulfide / graphene nano composite material by hydrothermal process

    CN108404936A

  • Molybdenum disulfide quantum dot / graphene / polymer-based super-wear-resistant self-lubricating composite material and preparation method and application thereof

    CN111662547A

  • Thermoplastic polyester elastomer composition synergistically modified by multi-dimensional filler as well as preparation method and application of thermoplastic polyester elastomer composition

    CN117362939A